Digital Literacy as a Pillar for Strengthening Character Education in Elementary Schools - Suteni, Ni Komang Putri; Wijaya, Ni Putu Dian Amhira; Darmayanti, Ni Made Nova Andila; Adnyana, I Kadek Ryan; Pandia, Nadia Arbreka Br S; Werang, Basillius Redan (PT FORMOSA CENDEKIA GLOBAL, 2024)
The integration of technology in education provides many benefits, including increased learning abilities and increased accessibility to educational resources. However, there is significant concern that without a simultaneous emphasis on character education, this could lead to a decline in moral values. It is critical for children to develop important character traits alongside digital literacy skills to adequately prepare them to face the challenges of the 21st century. The purpose of writing this article is to examine how digital literacy is used to strengthen character education. The method used in this research is a literature study research method carried out qualitatively or descriptively of literature obtained through a literacy process from various sources. The results of the research show that improving character education through digital literacy can be a strategy to face the 4.0 era.